2016
DOI: 10.1155/2016/6840432
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese Medicine Huannao Yicong Decoction Extract Decreases Tau Hyperphosphorylation in the Brain of Alzheimer’s Disease Model Rats Induced by Aβ1–42

Abstract: Objective. Huannao Yicong Decoction (HYD, 还脑益聪方) has been shown to improve the learning and memory capabilities of Alzheimer's disease (AD) subjects. However, the underlying mechanism remains to be determined. Methods. Sixty Sprague-Dawley rats were divided equally and randomly into five different groups including control, positive control, and HYD granules of low dose, medium dose, and high dose by daily gavage. The sham-treated rats were also given the same volume of sterile water by gavage. Twelve SD rats w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…After an entry point was chosen, the rats were released into the water facing the tank wall, and the number of times the rats crossed the platform site within 90 seconds was recorded. The MWM test protocol followed Cao's method [ 19 ]. After the MWM test, the rats were fasted for 12 hours, and serum and brain tissue samples were taken.…”
Section: Methodsmentioning
confidence: 99%
“…After an entry point was chosen, the rats were released into the water facing the tank wall, and the number of times the rats crossed the platform site within 90 seconds was recorded. The MWM test protocol followed Cao's method [ 19 ]. After the MWM test, the rats were fasted for 12 hours, and serum and brain tissue samples were taken.…”
Section: Methodsmentioning
confidence: 99%
“…However, since these strategies have yet to show significant benefit, new approaches are being probed, among which a scheme to enhancing protein homeostasis is an intriguing approach [147,149]. Other alternative approaches including using traditional Chinese medicine are also being pursued [150].…”
Section: Tauopathy Treatmentmentioning
confidence: 99%
“…Several traditional Chinese medicines have been suggested that might be useful for treating tauopathies [150,165]. Huannao Yicong Decotion was shown to improve learning and memory in rat AD model.…”
Section: Novel Treatment Approachesmentioning
confidence: 99%
See 1 more Smart Citation